Mass spectrometry in pathology - vision for a future workflow - Kriegsmann, Jörg; Casadonte, Rita; Kriegsmann, Katharina; Longuespée, Rémi; Kriegsmann, Mark (Pathology, research and practice, 2018)
Mass spectrometric (MS) techniques are applied in various areas of medical diagnostics. For the detection of microbiological germs and genetic mutations, MS is a method used in routine. Since MS also allows the analysis of proteins and peptides, it seems an ideal candidate to supplement histopatholological diagnostics. Matrix-assisted laser desorption/ionization time-of-flight Imaging MS links molecular analysis of numerous analytes with morphological information about their spatial distribution in cells or tissues. Herein, we review principle MS techniques as well as potential applications in pathology and discuss our vision for a future workflow.